PEMANFAATAN TEPUNG BIJI CEMPEDAK(Arthocarpus champeden Sperg.,) SEBAGAI SUBSTITUSI DALAM PEMBUATAN KUKIS - Saparun Saparun; Faizah Hamzah; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research was conducted to get the best rate and the best quality in the manufacture of a cookies, cempedak seed flour andwheat flour. This study was conducted experimentally using a Completely Randomized Design (CRD) with five treatments and four replications thus obtained twenty experimental units. The treatment in this study was CT0 = cempedak seed flour : wheat flour = 90:10,CT1 = cempedak seed flour : wheat flour = 80:15, CT2 = cempedak seed flour : wheat flour = 80:20, CT3 =cempedak seed flour : wheat flour = 75:15 and CT4= cempedak seed flour : wheat flour = 70:30.Chemical analysis undertaken is the moisture content, ash content, fat content and protein content.Data were Analyzed statistically using Analysis of Variance (ANOVA).If F count is greater than or equal to F table, then do a further test with Duncan's New Multiple Range Test (DNMRT) at5% level.Based on the chemical analysis cookiesCT1 best treatment is treatment with water content of 4.39%, ash content 1.31%, fat content 10,97% and protein content 10.12% that has met the cookiesquality standard (SNI 01-2973-1992). Keyword:cookies, cempedak seed flour, wheat flour